2021
DOI: 10.1155/2021/5526046
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Motivation and Desire in Explaining Students’ VR Games Addiction: A Cognitive-Behavioral Perspective

Abstract: Virtual Reality games create an interactive platform for gaming and education for young people. While some longitudinal study has studied the beneficial effects of VR games on learning, the problematic use of VR games by a significant number of learners has become increasingly serious. The current study investigated the mediating effect of behavioral desire and moderation of cyber aggression on consumers’ VAD, which contributes to behavioral and psychological urge to use VR games. Data are from 367 VR games us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…While the results of this study coincided with past research results, such as Mo et al, there is also increasing evidence that Internet use is associated with negative academic outcomes [ 34 ]. The surveys by Zhai et al indicated that users claimed that gaming addiction affected their learning and thinking [ 33 ]. The study by Chen et al found that users in an addictive state had impaired concentration and an inability to process distractions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the results of this study coincided with past research results, such as Mo et al, there is also increasing evidence that Internet use is associated with negative academic outcomes [ 34 ]. The surveys by Zhai et al indicated that users claimed that gaming addiction affected their learning and thinking [ 33 ]. The study by Chen et al found that users in an addictive state had impaired concentration and an inability to process distractions [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Users claim that gaming addiction can affect their learning and thinking [ 33 ]. At the same time, there is growing evidence that Internet usage is associated with negative academic outcomes [ 34 ].…”
Section: Theoretical Basis and Research Hypothesesmentioning
confidence: 99%
“…At present, some research includes research on students' addiction to VR games. In previous studies, including in the field of psychology, Cruz et al have examined how VR games can become addictive in adolescents [6]. In addition to the psychological aspect, Lemmens et al also study how VR games affect the body and what physiological reactions they will cause [7].…”
Section: Research Gapmentioning
confidence: 99%
“…The game runs in real time, so it is very important to maintain a stable frame rate during the whole game. However, technical problems such as pathfinding and behavior decision-making just need to consume a lot of CPU and memory resources, which brings certain difficulties to the development of game pathfinding and behavior decision-making technology [3][4]. In order to meet the increasing demands of players on all aspects of the game, survive in the fierce competition, and even stand out, game development technology is constantly developing and improving.…”
Section: Introductionmentioning
confidence: 99%